The concept of business ethics in islamic perspective: an introductory study of Small and Medium Enterprises (SMEs) - Mohd Zulkifli Muhammad; Ahmad Syakir Junoh @ Ismail; Ahmad Ridhuwan Abdullah; Razman Hafifi Redzuan; Siti Fariha Muhamad (International Business Information Management Association, 2013)
Islam places the highest emphasis on ethical values in all aspects of human life. In Islam, ethics governs all aspects of life. Ethical norms and moral codes discernible from the verses of the Qur’an and the Hadith are numerous, far reaching and comprehensive. Islamic business ethics is essential for SME industry. The challenge of Islamic business ethics is to make that inevitable ethical decision making explicit to make it better. Far from being anti-business, ethics actually provides essential support for maximizing long-term business value. In an Islamic system, ethics and business are not only compatible but also they are inseparable. Islam stresses the link between business and religion. It projects a perfect way of life. A human manner and behavior in small and medium enterprises cannot be effectively clarified without references to the Islamic ethics which can manage it. Thus, this paper will discuss the issues pertaining to the concept of business ethics in Islamic perspective toward Small and Medium Enterprises (SMEs). This is because of their significant contribution in the Malaysian economics at large. Furthermore, this study also explains how SME could adapt the Islamic business ethics system in their day-to-day business activities.